Solidarity And Social Interaction Among Transport Workers In The Midst Of The Modernization Of The Sudimampir Market - Nadila Yuliyanti; Jumriani Jumriani; Mutiani Mutiani; Sigit Triyono; Sovia Husni Rahmia (Journal of Social Development, 2026)
Market modernization has brought significant changes to the traditional economic structure, including threatening the sustainability of porters' livelihoods. This study focuses on Sudimampir Market in Banjarmasin, South Kalimantan, which is known as the largest wholesale center in Kalimantan. At Sudimampir Market, workers use private transportation such as pedicabs, bajaj, and motorized vehicles. The results of the porter study at the market can be divided into three types bajaj porters, becak porters, and ojek porters. Most porters have worked at the market for a long time with years of experience. The harsh working conditions for porters include low daily income ranging from Rp. 50,000 to Rp. 150,000. This income is often unpredictable and insufficient to meet basic needs. Some workers even seek part-time or additional jobs when their primary income is insufficient. Additionally, the lack of adequate rest facilities and the health risks they face add to the challenges of porter work. Social interactions between porters, merchants, and buyers reveal cooperation and mutual dependence. Challenges faced by porters include tariffs and price negotiations that often do not align with the workload. Workers face challenges from thugs demanding security or kiosk fees. Bad weather, such as rain, increases the physical risk of falling for workers while transporting goods. The daily income of porters adds uncertainty to their lives. Although some porters try to find other jobs to supplement their income, they often return to their original work due to skill limitations.